On the commodity trail the journey of a bargain store product from East to West - Hulme, Alison (Bloomsbury Academic, 2015)
"From raw materials on municipal rubbish dumps in the Far East, to newly re-made products and a journey across the seas, to bargain stores in Europe and North America and eventually to the homes of consumers, this is the complex story behind society's simplest and cheapest commodities. Weaving together compelling narratives from individuals at different parts of the commodity chain, including waste peddlers, wholesalers, stores owners and shoppers, this book considers the places and people at the heart of these localized, yet immense global networks. Following eight key objects, On the Commodity Trail combines ethnographies of material culture with a broader consideration of commodity culture at a time of global recession. This study explores the prevalence of the bargain store in our towns and cities and delves into the colourful and illuminating histories behind the objects on the shelf"-- Provided by publisher.